Character association and path analysis for yield components in turmeric (Curcuma longa L.) - Gupta, N S Tomar, S K Nair, C R (Journal of Spices and Aromatic Crops, 2005)
Correlation and path analys is of 11 characters of turmeric (Curcuma longa) were carried out using 22 genotypes at Raigarh (Chhattisgarh). Plant height, leaf length, thickness of primary and secondary rhizomes and number of secondary rhizomes revealed significant positive associations with rhizome yield. Path analysis showed positive direct effect of plant height, leaf length and thickness of primary and secondary rhizomes on rhizome yield. These traits may be given due e, ’phasis while making selections for improvement in rhizome yield of turmeric.